Women’s Political Participation in India: A Sociological Study - Dr. Rachana Prasad (JOURNAL OF MANAGEMENT, SCIENCES, OPERATION & STRATEGIES, 2023)
Many Indian organisations and many Indian women organizations were demanding the British for voting rights for women. Some elite or in special cases some other but very select few women were allowed to vote during the British rule.. Key words: Sociological Study, organizations, constituent assembly.